Risk factor analysis of fragility fractures in rheumatoid arthritis: A 3-year longitudinal, real-world, observational, cohort study. - Po-Heng Lin (Public Library of Science (PLoS), 2021)
Objectives To explore the risk factors for fragility fractures in rheumatoid arthritis (RA) patients using a 3-year longitudinal, observational cohort study. Methods This RA registry study included consecutive RA patients in the outpatient clinic of Chang Gung Memorial Hospital since September 1, 2014. The demographics, clinical characteristics, lifestyle, evidence of previous fracture, risk factors according to the Fracture Risk Assessment Tool (FRAX®), and the FRAX score of each participant were recorded. The participants were categorized into the new incident fracture (group A) and no incident fracture (group B) groups based on evidence or absence of new incident fractures and propensity score matching (age and gender, 1:2). Results Overall, 477 participants completed the 3-year observation period. After matching, 103 and 206 participants were allocated to groups A and B, respectively. The non-adjusted model revealed, presented as hazard ratio (HR) (95% confidence interval [CI]), that the presence of co-morbidity (1.80 [1.17-2.78], p = 0.008), Health Assessment Questionnaire Disability Index (1.35 [1.07-1.69], p = 0.010), lower baseline hip bone mineral density (0.11 [0.02-0.48], p = 0.004), longer disease duration (1.02 [1.00-1.04], p = 0.026), higher FRAX score of major fracture (1.03 [1.02-1.04], p<0.001) or hip fracture (1.03 [1.02-1.04], p<0.001), and previous fracture history (2.65 [1.79-3.94], p<0.001) were associated with new incident fracture. After adjustment, it was disclosed that a previous fracture is an independent risk factor for fragility fractures in RA patients (2.17 [1.20-3.90], p = 0.010). Conclusions In addition to aging and disease-related factors, previous fracture history is the most important risk factor for fragility fractures in RA patients.